The agri-environment - Warren, John, 1962-; Lawson, Clare; Belcher, Kenneth Ward, 1962-; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
The application of ecological theory and conservation biology to agricultural ecosystems has become an important and growing research field and undergraduate course component in recent years. This book is both an academic textbook and practical guide to farm conservation, and has evolved from the authors' extensive teaching experience. It covers the ecology of farmed land, how agricultural practices influence the environment, how agriculture has changed over time and how the species that inhabit the agri-environment have adapted. It also covers the history of agricultural policy and subsidies and the development of agri-environment schemes. A number of different farming systems are discussed, as are the difficulties in determining their relative merits. Guidance is offered on how to produce a workable farm conservation plan, and the final chapters look to the future and the development of new, greener farming systems.
An introduction to agro-ecology -- Agricultural support and environmentalism -- Environmental impacts of agriculture -- Principles behind agri-environment schemes -- Farm conservation planning -- Habitat management -- The management of agricultural wastes -- Low-impact farming systems -- Landscape and farmscape ecology -- The future of agri-environmental systems.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Agriculture -- Environmental aspects; Agricultural systems -- Environmental aspects; Agricultural ecology; Agricultural conservation; Agriculture and state; Electronic books